Pengaruh Service Quality, Trust Dan Satisfaction Terhadap Loyalty Customer Shopee di Bali (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Shopee is considered the most well-known marketplace in Indonesia based on a survey by App Annie, which examined the number of active users and how often people visit the site each month. In addition, Shopee is also recorded as the most downloaded application in Southeast Asia according to the same survey. The aim of this research is to examine the impact of service quality, trust, and satisfaction on customer loyalty. This research was conducted in Bali with a sample of 130 respondents. Data analysis will utilize reliability and validity tests, multiple linear regression, classical assumptions, t-tests, F-tests, and the coefficient of determination. This research shows that each independent variable partially contributes significantly and positively to customer loyalty. This means that each independent variable simultaneously contributes 66.1% to customer loyalty. The researchers suggest that Shopee should collaborate with more shipping services, continuously monitor sellers, and provide warnings and strict sanctions to those proven not to deliver products as promised to buyers. They should also offer a money-back guarantee if the product received does not match what was promised.